Googled justice: an examination of the citation of Internet sources in judicial opinions in Uganda. Issue 38 (September 2020) - Rukundo, Solomon
Abstract: Search engines like Google have made it incredibly easy to access vast amounts of information with little effort. Many lawyers now prefer to go online for their legal research. Lawyers are citing online sources to establish legal and factual positions in their submission briefs to court and, in turn, judges are citing them in their opinions. Judges are also conducting online research to better understand the complexities of disputes before them. This paper examines the challenges arising from the citation of online sources in judicial opinions in Uganda. It argues that while there are significant benefits to relying on Internet sources, there are also challenges like inaccuracy of online information, excessive reliance on non-legal sources and inaccessibility of some online sources. It concludes with recommendations for best practices that can be adopted by the Ugandan courts in dealing with these limitations when citing online authorities.